Clinicopathologic features and abnormal signaling pathways in plasmablastic lymphoma: a multicenter study in China - Di Shi; Lin Gao; Xiao-Chun Wan; Jin Li; Tian Tian; Jue Hu; Qun-Ling Zhang; Yi-Fan Su; Yu-Peng Zeng; Zi-Juan Hu; Bao-Hua Yu; Xiao-Qiu Li; et al. (BMC Medicine, 2022)
Abstract Background Plasmablastic lymphoma (PBL) is a rare but aggressive B-cell lymphoma subtype with poor prognosis. Knowledge about the etiology, clinicopathologic and molecular features, and outcomes of PBL is limited. This study aimed to examine the clinicopathologic characteristics, therapeutic approaches, and clinical outcomes of PBL patients in a Chinese population. Methods A total of 102 PBL patients were recruited from three cancer centers. The pathologic features and clinical outcomes of 56 patients with available treatment details and follow-up data were reviewed and analyzed. RNA sequencing was performed in 6 PBL and 11 diffuse large B-cell lymphoma (DLBCL) patients. Results Most patients in our cohort were male (n = 36, 64.3%), and 35 patients presented with Ann Arbor stage I/II disease at diagnosis. All these patients showed negative findings for human immunodeficiency virus, and the vast majority of patients in our cohort were immunocompetent. Lymph nodes (n = 13, 23.2%) and gastrointestinal tract (n = 10, 17.9%) were the most commonly involved site at presentation. Post-treatment complete remission (CR) was the only prognostic factor affecting overall survival (OS) and progression-free survival (PFS) in the multivariate analysis. RNA-seq demonstrated that B-cell receptor (BCR), T-cell receptor (TCR), P53, calcium signaling, and Wnt signaling pathways were significantly downregulated in PBLs compared with GCB (or non-GCB) DLBCLs. Conclusions In this multicenter study in the Chinese population, PBL mainly occurred in immunocompetent individuals and most patients present with early-stage disease at diagnosis. Post-treatment CR was an important prognostic factor affecting OS and PFS. RNA-seq showed that the B-cell receptor (BCR), P53, calcium signaling, cell adhesion molecules, and Wnt signaling pathways significantly differed between PBL and GCB (or non-GCB) DLBCL, which provided theoretical basis for its pathogenesis and future treatment.